Analisis Integrated Marketing Communication (IMC) dalam Membangun Loyalitas Konsumen Susu Mbok Darmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has changed communication patterns and consumer behavior, so companies need to adapt to marketing communication strategies. Integrated Marketing Communication (IMC) is an important strategy to maintain message consistency, strengthen brand image, and build consumer loyalty. This research was conducted at PT Sumoda Tama Berkah or Susu Mbok Darmi, a local Food and Beverage company from Bogor that produces pasteurized milk from local farmers. Data collection was through observation, active participation, and literature review while the author was directly involved in activities within the Marketing Communication division. The purpose of the research was to determine the elements used and the elements that most contribute to building loyalty. This study found that Susu Mbok Darmi applies five main elements of IMC: Sales Promotion, Events and Experiences, Public Relations, Direct Marketing, and Interactive Marketing. Of the five elements, Events and Experiences and Public Relations have the greatest influence on building consumer loyalty because they create direct experiences and strong emotional connections between the company and consumers.